Dissent in dangerous times - Sarat, Austin (Book collections on Project MUSE., 2005)
While dissent has played a central role in our national history and in the American cultural imagination, it is usually dangerous to those who practice it, and always unpalatable to its targets. War does not encourage the tolerance of opposition at home any more than it does on the front: if the War on Terror is to be a permanent war, then the consequences for American political freedoms cannot be overestimated. The contributors examine the role of political opposition in our times, the nature of political repression in liberal societies, the political and legal implications of fear, and how past generations responded to similar situations. From publisher description.